Influencing Factors Satisfaction Patient User Guarantee Labor (Jampersal) against Health Services at Gunung Maligas Health Centers - Firdasari; Br Siregar, Jeni Raulina (International Journal of Public Health Excellence (IJPHE), 2023)
Guarantee Childbirth ( Jampersal ) is guarantee financing service childbirth which includes inspection pregnancy , help delivery , service childbirth including service family planning (KB) post childbirth and services baby new born by force health at the facility health. Jampersal aim lower Number Death Mother (NDM) and numbers Death Directed Babies (DDB) in Indonesia in enhancement quality service health. Jampersal must notice service quality health to create satisfaction patient. Type study This is study descriptive with approach purposeful retrospective identify influencing factors satisfaction patient user Jampersal to service health at the Health Center Gunung Maligas Regency Simalungun. Sample in research this is existing mothers Once using Jampersal program start from gestation until the puerperium, and do installation tool contraception. Taking sample with simple random sampling technique with amount sample as many as 51 people. Research results showing that majority patient user Jampersal feel satisfied to service health (92.2%) in Gunung Maligas Subdistrict, where the average value of satisfaction patient each factor is satisfying that is access service health (76.5%), quality service health (92.2%), service process health (88.2%), and systems service health (78.4%). Expected officer health Keep going give quality service for reach satisfaction patient.